2017
DOI: 10.3390/biomedicines5040059
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of DAP Kinase Tumor Suppressor Function: A Therapeutic Strategy to Selectively Induce Apoptosis in Cancer Cells Using Immunokinase Fusion Proteins

Abstract: Targeted cancer immunotherapy is designed to selectively eliminate tumor cells without harming the surrounding healthy tissues. The death-associated protein kinases (DAPk) are a family of proapoptotic proteins that play a vital role in the regulation of cellular process and have been identified as positive mediators of apoptosis via extrinsic and intrinsic death-regulating signaling pathways. Tumor suppressor activities have been shown for DAPk1 and DAPk2 and they are downregulated in e.g., Hodgkin’s (HL) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Although they are not well known for the regulation of DAPK1, it has been shown that they act as important phosphorylation sites in cancer therapy. DAPK1 is dephosphorylated at Tyr491/Tyr492 by the leukocyte common antigen-related (LAR) tyrosine phosphatase, which is involved in catalytic stimulation, apoptosis and anti-adhesion/anti-migration activity [58,59]. On the other hand, Src induces the phosphorylation of DAPK1 at Tyr491/Tyr492, which enhances intra/intermolecular interactions and the inactivation of DAPK1 [58].…”
Section: Regulation Of Dapk1 By Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they are not well known for the regulation of DAPK1, it has been shown that they act as important phosphorylation sites in cancer therapy. DAPK1 is dephosphorylated at Tyr491/Tyr492 by the leukocyte common antigen-related (LAR) tyrosine phosphatase, which is involved in catalytic stimulation, apoptosis and anti-adhesion/anti-migration activity [58,59]. On the other hand, Src induces the phosphorylation of DAPK1 at Tyr491/Tyr492, which enhances intra/intermolecular interactions and the inactivation of DAPK1 [58].…”
Section: Regulation Of Dapk1 By Phosphorylationmentioning
confidence: 99%
“…On the other hand, Src induces the phosphorylation of DAPK1 at Tyr491/Tyr492, which enhances intra/intermolecular interactions and the inactivation of DAPK1 [58]. This establishes a functional link between tumor progression and the DAPK1 regulation mechanism, but the link to neuronal cell death has not been determined [58,59,60].…”
Section: Regulation Of Dapk1 By Phosphorylationmentioning
confidence: 99%
“…The death‐associated protein kinase (DAPK) family is one of the important families of STKs that regulate several biological functions in the human cells. A few research groups have reviewed DAPK1‐related subjects mostly focusing on the structure, regulation, and biological roles . In this review, our objective is to give an updated comprehensive overview about the structure, regulation, and biological roles of DAPKs and provide, for the first time, a comprehensive review on the strategies used to modulate the activity of this kinase family with small molecules from a medicinal chemistry perspective and evaluate their therapeutic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…One such mechanism involves the phosphorylation of beclin 1 which is required for autophagosome nucleation formation. It is also believed that DAPK2 may function upstream of DAPK1 as the over expression of a dominant negative DAPK1 reduced DAPK2 induced cell death (Tur et al, 2017). So that our data showed unexpected significant decrease in autophagic activities (as revealed by a reduction in fluorescence intensity of autophagosome marker that determined by flow cytometry which in turn in disagreement with the result of beclin 1 that also decreased -data not shown) in treated groups (GP6, 7) and especially in combination group (GP8) when compared with EAC group (GP2).…”
Section: Discussionmentioning
confidence: 99%